Production and characterization of immunoglobulin G anti-rLipL32 antibody as a biomarker for the diagnosis of leptospirosis - Susanti Susanti; Pratiwi Pudjilestari Sudarmono; N. L. P. Indi Dharmayanti; Prasandhya Astagiri Yusuf (Veterinary World, 2024)
Background and Aim: Microscopic agglutination test (MAT) for the diagnosis of leptospirosis requires live cultures and is serovar-specific, while polymerase chain reaction (PCR) requires expensive equipment and sample preparation. The rLipL32 protein is conserved and can be used for the production of immunoglobulin G (IgG) anti-rLipL32 antibody, which can be used as a biomarker for leptospirosis diagnosis. This study aimed to produce and characterize an IgG anti-rLipL32 antibody as a biomarker for leptospirosis diagnosis.